2017
DOI: 10.1158/1940-6207.capr-17-0106
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aberrant p70S6K Activation for Estrogen Receptor–Negative Breast Cancer Prevention

Abstract: The prevention of estrogen receptor negative (ER−) breast cancer remains a major challenge in the cancer prevention field although anti-estrogen and aromatase inhibitors (AIs) have shown adequate efficacy in preventing estrogen receptor positive (ER+) breast cancer. Lack of commonly expressed, druggable targets is a major obstacle for meeting this challenge. Previously, we detected the activation of Akt signaling pathway in atypical hyperplasic early stage lesions of patients. In the current study, we found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…The 70 kDa ribosomal protein S6 kinase (p70S6K) has contributed to the development of breast cancer (Miller et al, 2011). For instance, a study conducted with breast tissue biopsy from women with high grade of Tamoxifen resistance revealed high levels of Akt/p70S6K activation and confirmed that Akt/p70S6K signaling pathway was activated in early stage breast disease (Wang et al, 2017). In our study, the mixture of phenolics in CphE reduced p70S6K levels in 4T1 cells more effectively than quercetin alone.…”
Section: Discussionsupporting
confidence: 75%
“…The 70 kDa ribosomal protein S6 kinase (p70S6K) has contributed to the development of breast cancer (Miller et al, 2011). For instance, a study conducted with breast tissue biopsy from women with high grade of Tamoxifen resistance revealed high levels of Akt/p70S6K activation and confirmed that Akt/p70S6K signaling pathway was activated in early stage breast disease (Wang et al, 2017). In our study, the mixture of phenolics in CphE reduced p70S6K levels in 4T1 cells more effectively than quercetin alone.…”
Section: Discussionsupporting
confidence: 75%
“…To further confirm that, we checked the expression of the major component genes of EIF2 signaling and found upregulation of multiple genes, including EIF2AK1 (HRI protein coding gene), EIF2AK2 (PKR protein coding gene), EIF2AK4 (GCN2 protein coding gene), EIF2B5, and AKT2 ( Figure 7E ; Rios-Fuller et al, 2020 ). Other ingenuity canonical pathways included regulation of eIF4 and p70S6K signaling and mTOR signaling ( Figure 7D ), both of which were closely associated with TNBC biological activities ( Madden et al, 2014 ; Wang et al, 2017 ; Zagorac et al, 2018 ). Graphic regulatory networks integrating ingenuity canonical pathways and upstream regulators of the metastatic cells gave a core pathway of cell viability of breast cancer cells, which was closely related with EIF2 signaling and regulators of RB1, TP53, and MYC ( Figure 7F ).…”
Section: Resultsmentioning
confidence: 99%
“…As the key rate-limiting enzyme of FAO, CPT1 conjugates fatty acids with carnitine for translocation into the mitochondria; therefore, it controls FAO directly and thus facilitates cancer metabolic reprogramming. CPT1 also shares multiple connections with many other cellular signaling pathways often dysregulated in cancers, such as aerobic glycolysis, FAS, p53/AMPK axis, mutated RAS, mTOR and STAT3 [ 91 , 92 ]. This evidence positions CPT1 as a multifunctional mediator in cancer pathogenesis and resistance to treatment.…”
Section: Fao and Cancer Stemnessmentioning
confidence: 99%